Effect of altering N application timing on critical paddy development and rice production / Rabiahtul Adawiah Rosli - Rosli, Rabiahtul Adawiah (Faculty of Plantation and Agrotechnology, 2019)
Nitrogen is the most limiting nutrient in rice production. Nitrogen fertilizer is susceptible to losses through volatilization, denitrification and leaching. The time of application often does not match with period of crop demand. Adjusting the timing of nutrient application especially nitrogen could potentially improve the nutrient uptake and reduce nutrient losses to allow better nutrient efficiency. A greenhouse experiment was conducted to determine the best of nitrogen fertilizer application timing to improve development and rice production of two Malaysian rice cultivars (MR219 and MR269). The experiment consisted of four treatments applied each at 120 kg ha-1 of N in the form of urea. For T1, N was applied on 15, 35 and 55, T2 was applied on 12, 32, and 52, T3 was applied on 18,38 and 58, and T4 was applied on 21, 41 and 61 days after seeding (DAS) with three replications. Plant physiological parameters such as plant height, tiller, panicle, straw, SPAD and 100-grain weight did not show significant differences. Only total grain weight showed significant differences among the treatments. The application of N also resulted in an increase by 12.13% in plant biomass. The results demonstrate that the split application of fertilizer N at PI stage (58 DAS) significantly increased percentage of 100-grain weight and total grain yield compared to the control treatment, which is applied on 15, 35, and 55 DAS. Farmers should be advised to apply N between 52 DAS and 58 DAS, even though application of N at 58 DAS was significantly better than 55 DAS in terms of yield production.